Macroeconomic effects of inflation targeting in advanced and emerging market economies - Igor Chugunov; Mykola Pasichnyi; Anton Nepytaliuk (Banks and Bank Systems, 2019)
The article assessed the treatment effects of targeting inflation regime on the real output and consumer inflation persistence in both advanced and emerging market economies. An empirical analysis is based on data from 35 OECD and 40 emerging countries and covers inflation and non-inflation targets over the period 1990–2017. The results showed that inflation targeting (henceforth – IT) had no significant impact on the GDP per capita growth rate but slightly reduced the output volatility. This study founded out that full-fledged IT had the effect of slowing down consumer inflation and reducing its volatility. Moreover, in the OECD countries, the monetary framework had certain advantages during the Great Recession. The authors argued that in order to maintain price stability in emerging economies, a high level of central bank independence and accountability is required.